Comparative evaluation of different bedding materials on growth performance of Murrah buffalo calves - CHOPRA, DEEPAK; SAHU, SUBHASISH; RAINA, AAMIR AHMAD; PARRAY, MOHSIN AHMAD; BIDHAN, DEVENDRA; CHHARANG, DHARMENDRA; CHHIKARA, S K; SINGH, MAN (The Indian Journal of Animal Sciences, 2022)
Ideal bedding management is essential for optimal health, welfare, and growth performance of dairy calves. The study was conducted in order to compare the effect of different bedding materials on growth performance of Murrah buffalo calves. Murrah buffalo calves (n=20) of less than 4 months of age were selected and divided into four groups (5 animals/group), viz. T1: Concrete floor, T2: Concrete floor bedded with sand, T3: Concrete floor bedded with wheat straw and T4: Concrete floor bedded with rubber mat. Body weight and body measurement (body length, height of wither and heart girth) were taken at fortnightly and monthly intervals, respectively. There was no significant difference in body weight between treatment groups. However, average weight gain (kg) and ADG was significantly high in calves reared on T3 as compared to other treatment groups, though no significant difference was observed between T1, T2 and T4. Body length was significantly lower in T2 as compared to T3, however, difference in body length among T1, T2 and T4 groups was relatively non-significant. Moreover, body height and heart girth were significantly higher in calves reared on wheat straw floor as compared to concrete and sand bedded floor. Estimation of net profit per calf after reducing the bedding cost revealed that it was highest for wheat straw bedding followed by rubber mat, concrete and least for sand bedding. It can be concluded that wheat straw followed by rubber mat could be used effectively as bedding over concrete floor during winter season for rearing of calves.